Clinicopathological Features of Buccal Squamous Cell Carcinoma with Focus on Patients Who Never Smoke and Never Drink - Iida, Yoshiyuki; Okada, Shinichi; Irifune, Yuki; Goto, Seiya; Ishida, Kotaro; Sato, Fuyuki; Yurikusa, Takashi; Asakura, Koiku; Tsuzuki, Ayaka; Mukaigawa, Takashi (International Archives of Otorhinolaryngology, 2023)
Introduction Oral carcinoma has been reported at a substantial proportion in patients who never smoke and never drink. However, the proportion may vary by subsite and ethnicity.Objective We aimed to determine the clinicopathological features of buccal squamous cell carcinoma (SCC) in a Japanese population.Methods We retrospectively analyzed the records of patients diagnosed with buccal SCC at our institution from September 2002 to November 2015. We reviewed the gender, age, tumor status, treatment, smoking, alcohol drinking, multiple primary cancers, and prognosis of the patients. The overall and cause-specific survival rates were calculated, and the effects of clinicopathological variables were assessed by univariate analysis. Furthermore, the cause of death was evaluated.Results Among the 63 patients (men: 38; women: 25) included in the present study, 29 (46.0%) never smoked or drank. Women were almost 5 years older than men (p = 0.014). The number of women in the group who never smoked or drank was disproportionately higher than that of those in the smoker or drinker groups (p < 0.001). In total, 29 patients (46.0%) had 59 multiple primary cancers, including 26 oral cancers. Surgeries and radiotherapy were performed in 57 (90.5%) and 6 (9.5%) cases, respectively. The 5-year overall survival and disease-specific survival rates were 74.6 and 78.8%, respectively.Conclusion Our study confirms that buccal SCC may develop in older adult Japanese patients, especially in women who have never smoked or drank. These patients could be at risk for second primary malignancy.
Keywords: buccal mucosa; cancer of head and neck; multiple primary neoplasm; alcohol drinking; tobacco cessation; Japanese